The ameliorative effects of low-temperature pasteurization on physicochemical and microbiological quality of raw Akoya pearl oyster (Pinctada fucata). (November 2021) - Chung, Wing H.; Howieson, Janet; Chaklader, MD Reaz
Abstract: This study investigated the effect of 5–20 min low-temperature pasteurization at 50 °C on Akoya oyster's physicochemical including moisture, texture, colour, pH, total volatile base nitrogen (TVB-N) and microbiological quality in terms of total viable count (TVC), tests for Escherichia coli ( E. coli ), Vibrio spp. and Vibrio parahaemolyticus ( V. parahaemolyticus ) 14 days post-treatment. Oysters were sourced from Abrolhos island pearl farm and kept alive in simulated condition until treatment day. Physicochemical analyses and TVC were then conducted on day 0, 4, 7, 10, 14 while the remaining microbiological analyses were performed on day 0, 7, 14. Regression analysis showed that none of physicochemical characteristics showed a linear trend, with the exception of TVB-N which increased linearly in all treated oyster with increasing the storage time. Two-way ANOVA indicated that heat treated oysters with more than 10 min treatment time shown to have increase in moisture and firmness compare to control. Colour improvement was also observed in >10 min heat treated adductor muscle while no consistent changes in pH were observed. TVB-N value ranging from 11.49 to 23.59 mg/100 g was influenced by treatment and storage time with significant increases identified in all samples at day 10 and 14. The microbiological results reveal that, TVC, E. coli and V. parahaemolyticus were within standard limit and considered safe to be consumed. Additionally, heat treatment of more than 10 min has shown to suppress Vibrio spp. growth until day 7–14. General amelioration in Akoya oysters physicochemical and microbiological quality suggests that low-temperature pasteurization is a viable option in Akoya oyster processing. Results could aid in commercialization of raw Akoya oyster product and waste reduction in pearl industries. Highlights: First investigation of potential using Akoya pearl oyster by pasteurization. 10 and 20 min heat-treated oyster was found to have better moisture and firmness. TVB-N in all treated oysters increased linearly with increasing storage time. Microbiological quality was improved for 10 and 20 min treated oyster. TVC count was reduced and Vibrio spp. was suppressed for a prolonged period.